PENGEMBANGAN BUKU KOMIK SEBAGAI MEDIA PEMBELAJARAN IPA PADA MATERI PEMANASAN GLOBAL KELAS VII SMP - Annisa Pusvita Sari; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to produce comic books as a media for science learning in global warming material for seventh class. The comic development process was carried out in the Biology Education Study Program of Riau University and limited trials were conducted at SMP IT FIS Pekanbaru. The time of study was July up to November 2018. The development model used the ADDIE model until the development stage. The research subjects in the research that will be developed are KD 3.9; Analyzing climate change and its impact on the ecosystem in this study which was consisted of 3 meetings. The instruments were validation sheets, response questionnaires and comic products that have been developed. Data collection was carried out by filling out a validation sheet by 5 validators (3 Biology Education lecturers and 2 middle school science teachers). The limited trial I was carried out to 10 students of 7th semester Biology Education in the Biology Education Study Program. Based on suggestions from respondents, the results of the trial I, the researchers made a revision. After the revision, a limited trial II was conducted which was carried out for 20 seventh grade students of SMP IT FIS Pekanbaru. The results of the average comic validation scores that have been developed are simplicity aspects 3.43, emphasis aspects 3.70, balance aspects 3.60, integration aspects 3.30, and comic design aspects 3.69. The average score of the validation results from the five aspects is 3.54 with a very valid category. The response of trial users 1 was 93.33% with a very good category and the response of users to trial 2 was 95.41% with a very good category. Based on the results of validation and trials, it can be concluded that the quality of comic books for junior high school students is very valid and it can be implemented, appropriate for students to be use as a source of learning, and as references for junior high school science teachers. Key Words: Comic, Science, Junior High School